PENGARUH SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION DENGAN VALUE CO-CREATION SEBAGAI VARIABEL MEDIASI - Aimanisa Aulia Putri; Muzakar Isa (MANAJEMEN DEWANTARA, 2024)
This research aims to test the mediating influence of value co-creation on the influence of social marketing on purchase intention because value co-creation is believed to explain why social marketing can influence purchase intention. The research respondents were 227 Arkanza Batik consumers who were collected through questionnaires. The data will be analyzed using PLS-SEM analysis with the help of SmartPls. The test results concluded that social media marketing and value co-creation had a positive and significant effect on purchase intention on Instagram Batik Arkanza. Apart from that, social media marketing has a positive and significant effect on value co-creation and purchase intention, mediated by value co-creation on Instagram Batik Arkanza